Oxidation of cyclohexanol to epsilon-caprolactone with aqueous hydrogen peroxide on H3PW12O40 and Cs2.5H0.5PW12O40 - Balbinot, L. (2008)
Liquid phase cyclohexanol catalytic oxidation to cyclohexanone and epsilon(ε)-caprolactone were studied using aqueous hydrogen peroxide as oxidant and H3PW12O40 (HPA) and H0.5Cs2.5PW12O40 (Cs-salt) as catalysts. The hydrophobic and insoluble Cs-salt showed the highest activity (per unit catalytic weight and turnover number) and selectivity to (ε)-caprolactone. The ultrafine Cs-salt crystallites could be filtrated and recycled. Solvent effects on the activity and selectivity and the rate of peroxide decomposition were assessed and they were correlated to their polarity and protic/aprotic nature. When employing acetonitrile at 90 °C the highest activity and selectivity were achieved and also the lowest rate of hydrogen peroxide decomposition.